Place-based Approaches to Alternative Energy: The Potential for Forest and Grass Biomass for Aroostook County - Johnston, Jason; Cardenas, Soraya (Maine Policy Review, 2012)
Teams at the University of Maine Presque Isle and the University of Maine at Forth Kent are engaged in evaluating the potential for forest and grass biomass energy in Aroostook County, funded through Maine’s Sustainability Solutions Initiative. The article discusses how this potential is being evaluated and the possible ways in which expanding grass and wood biomass might benefit farmers and residents of The County. It suggests that using some of Maine’s farmland for fuel might be sustainable with appropriate management and with consideration for potential environmental and socioeconomic drawbacks
Keywords: Maine; Aroostook County; alternative energy; biomass